Ab initio electronic structure of metallized NiS2 in the noncollinear magnetic phase - Reiss, P; Friedemann, S; Grosche, FM (American Physical Society, 2022)
We investigate the electronic structure of the archetypical Mott insulator NiS2 by means of density functional theory calculations in which we explicitly account for the non-collinear antiferromagnetic order, as recently established in the isoelectronic analogue . For metallic NiS2 under high pressures, our calculations predict a Fermi surface topology and volume which are in excellent agreement with recent quantum oscillation studies. However, we find that density functional theory wrongly predicts a metallic ground state even at ambient pressures, similar to previous nonmagnetic or collinear antiferromagnetic models. By including a Hubbard interaction U and an on-site exchange interaction J, the metallic phase is suppressed, but even such an extended model fails to describe the nature of the metal-to-insulating phase transition and describes the insulating phase itself incorrectly. These results highlight the importance of more sophisticated computational approaches even deep in the insulating phase, far away from the Mott-insulating phase transition.